2,3-Butanedione monoxime attenuates the β-adrenergic response of the L-type Ca2+ current in rat ventricular cardiomyocytes - Julio Alvarez-Collazo; Ana Iris López-Medina; Loipa Galán-Martínez; Julio L. Alvarez (GarVal Editorial Ltda., 2016)
Context: 2,3-Butanedione monoxime (BDM), an uncoupler of cardiac contraction, is commonly used in enzymatic dissociations to prevent hypercontraction of cardiomyocytes and in cardioplegic solutions to decrease oxygen demand during surgery. However, BDM affects multiple cellular systems including the L-type Ca2+ current (ICaL). If its phosphatase activity is the mechanism underlying the decrease ICaL in cardiomyocytes is a still unresolved question. Aims: To study the effects of BDM on ICaL of rat ventricular cardiomyocytes focusing our attention on the response of ICaL to β-adrenergic stimulation. Methods: The whole-cell patch-clamp method was used to study ICaL in enzymatically dissociated rat ventricular cardiomyocytes. Results: Extracellular BDM (5 mM) decreased peak ICaL by ≈45%, slowed its fast inactivation but accelerated its slow inactivation. Cardiomyocytes incubated in BDM (≥ 30 min; 5 mM) perfused with normal extracellular solution, showed normal ICaL properties. However, extracellular BDM (in cardiomyocytes incubated in BDM or not) markedly reduced the response of ICaL to isoproterenol (1 µM). BDM also strongly attenuated the increase of ICaL in cardiomyocytes intracellularly perfused with cyclic AMP (50 µM). Conclusions: The decrease of basal ICaL by BDM is not related to its dephosphorylation action. Its effect on the Ca2+ channel occurs most probably in a site in the extracellular side or within the sarcolemmal membrane. Due to its phosphatase action, BDM strongly attenuates the response of ICaL to β-adrenergic stimulation. These actions of BDM must be taken into account both for its use in the dissociation of cardiomyocytes and in cardioplegic solutions and myocardial preservation.